Evaluation of gastro-protective effect of the hydro-alcoholic extract of Juglans regia. L leaves in experimental animals - Kumaraswamy Dabburu, Suresh Babu Kondaveeti, Sarath Babu.K (Journal of Applied Pharmaceutical Science)
The aim of our study was to evaluate the gastro protective effect of aqueous extract of Juglans regia.L leaves in albino rats. Albino rats of wistar variety weighing 140-165gms were used in the experiment. The sexes were evenly divided into different treatment groups. The aqueous leaf extract of Juglans regia.L was investigated for its anti- ulcer activity against pylorus ligation, aspirin induced and ethanol induced gastric ulcer in rats at 500mg/kg body weight p.o. Histopathological assessment of rat stomach was carried out. A significant reduction (p
Keywords: Juglans regia. L, pylorus ligation, aspirin, ethanol.